2021
DOI: 10.1002/cc.20504
|View full text |Cite
|
Sign up to set email alerts
|

Advocating for community colleges in the college completion agenda

Abstract: Community colleges are essential to meet state educational attainment goals, yet the colleges are largely underfunded to serve underprepared students entering through the open door of access. As resource‐dependent institutions, community colleges need to engage in the politics of higher education through advocacy. This chapter presents results from a qualitative study of community college advocacy practices in three states with bifurcated higher education governance. Interviews with the community college syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…In their study of pathways for career and technical programs, they proposed four dimensions of structure focused particularly on: program prescription, program alignment, access to information, and active program advising and support (Van Noy et al, 2016). However, these dimensions do not take into account the broader and complex college structures beyond programs including leadership, governance, funding, and reporting structures (McPhail, 2016;White, 2022a;Wyner, 2021).…”
Section: Internal Structural Context Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…In their study of pathways for career and technical programs, they proposed four dimensions of structure focused particularly on: program prescription, program alignment, access to information, and active program advising and support (Van Noy et al, 2016). However, these dimensions do not take into account the broader and complex college structures beyond programs including leadership, governance, funding, and reporting structures (McPhail, 2016;White, 2022a;Wyner, 2021).…”
Section: Internal Structural Context Challengesmentioning
confidence: 99%
“…Jenkins et al (2022) found that the ability to fund or budget for organizational change including staffing, technology, and other direct instructional costs becomes difficult given declining enrollment which impacts institutional funding models and other financial challenges, including the COVID-19 pandemic, and that this often creates a barrier to sustaining the change effort. White (2019White ( , 2022a) indicated that states with governing boards may create policy environments that impact internal institutional funding to support college completion and educational attainment and noted that these mandated policies can often pose a significant barrier to college-level organizational change.…”
Section: Financial and Public Health Factors Impacting Internal Changementioning
confidence: 99%
“…Because “[l]eaders are challenged to transform the very nature of the urban community college” (Myran & Parsons, 2013, p. 7), a look at one particular group of decision‐makers is important. Trustees of community colleges play “…a vital role in college and student success through governance and oversight of the mission of open access higher education” (White, 2022, p. 63). A challenge before community college boards is that they govern institutions with direct ties to the community and “are called upon to serve a wide variety of needs of people throughout their neighborhoods, cities, and regions, as well as their states” (Polonio, 2005, para 3).…”
Section: Community Collegesmentioning
confidence: 99%
“…Governing boards of community colleges perform key functions, including selecting and appointing the chancellor or president of the institution, establishing policies ensuring fiscal integrity, and performing other management functions (Kater et al., 2022; Lovell & Trouth, 2002; White et al, 2022). Boards of urban community colleges must address pressing issues facing their institutions.…”
Section: Opportunities For Trustee Support At Urban Community Collegesmentioning
confidence: 99%
See 1 more Smart Citation